Rational design method for bituminous pavements reinforced by geogrid - Freire, Reuber; Di Benedetto, Hervé; Sauzéat, Cédric; Pouget, Simon; Lesueur, Didier (Geotextiles and geomembranes, 2023)
Geosynthetics have been a reinforced solution for pavement structures for more than 80 years and could be effective in extending its service life. There is a lack of consolidated design methods for pavement with this reinforcement. Therefore, this work aims at proposing a new rational design approach for reinforced structures based on the French design method. In this approach, the geogrid contribution was included by improving the fatigue and rutting properties of some layers, using coefficients named kmaj and kmaj_Z. Three hypotheses were considered concerning the condition of an old bituminous layer remaining from rehabilitation works. The first one considered this layer in healthy condition to simulate a new reinforced structure. The second one considered it as cracked and the third one as disintegrated to simulate the design for rehabilitation. Two placement positions and two geogrid-interface conditions (bonded and not bonded) were analyzed. The results indicated that the geogrid was most effective in a completely deteriorated structure and it should be placed in the lowest possible position in the bound layers. This method can be used for any geogrid position within the structure. Lastly, the reinforcement by geogrid allows a reduction of the thickness of the layer above it. •Geogrid contribution is included by improving the fatigue and rutting properties of some layers of the structure.•The proposed method is simple and can be used for any geogrid position within the structure.•The fatigue of bituminous mixtures was always the critical when compared to the rutting of granular layers.•For fatigue design criterion, the geogrid should be place as low as possible within the bituminous layers.•The reinforcement by geogrid allows a reduction of the thickness of the layer above it.